Comparison of lauric acid and 12-hydroxylauric acid in the alleviation of drought stress in peach (Prunus persica (L.) Batsch) - Zhang, Binbin; Du, Hao; Sun, Maoxiang; Wu, Xuelian; Li, Yanyan; Wang, Zhe; Xiao, Yuansong; Peng, Futian (Frontiers in Plant Science, 2022)
Water shortage is a key factor that can restrict peach tree growth. Plants produce fatty acids and the fatty acid derivatives lauric acid (LA) and 12-hydroxylauric acid (LA-OH), which are involved in abiotic stress responses, but the underlying stress response mechanisms remain unclear. In this study, physiological examination revealed that in Prunus persica (L.) Batsch, pretreatment with 50 ppm LA-OH and LA reduced drought stress, efficiently maintained the leaf relative water content, and controlled the relative conductivity increase. Under drought stress, LA-OH and LA treatments prevented the degradation of photosynthetic pigments, increased the degree of leaf stomatal opening and enhanced the net photosynthetic rate. Compared with drought stress, LA-OH and LA treatment effectively increased the net photosynthetic rate by 204.55% and 115.91%, respectively, while increasing the Fv/Fm by 2.75% and 7.75%, respectively, but NPQ decreased by 7.67% and 37.54%, respectively. In addition, the level of reactive oxygen species increased under drought stress. The content of O2- in LA-OH and LA treatment decreased by 12.91% and 11.24% compared to CK-D, respectively, and the content of H2O2 decreased by 13.73% and 19.94%, respectively. At the same time, the content of malondialdehyde (MDA) decreased by 55.56% and 58.48%, respectively. We believe that the main reason is that LA-OH and LA treatment have improved the activity of superoxide dismutase (SOD), peroxidase (POD), and catalase (CAT). The application of exogenous LA increased the levels of soluble sugars, soluble proteins, proline and free amino acids under drought stress, and maintained the osmotic balance of cells. Compared with CK-D treatment, it increased by 24.11%, 16.89%, 29.3% and 15.04%, respectively. At the same time, the application of exogenous LA-OH also obtained similar results. In conclusion, exogenous LA-OH and LA can alleviate the damage to peach seedlings caused by drought stress by enhancing the photosynthetic and antioxidant capacities, increasing the activities of protective enzymes and regulating the contents of osmotic regulators, but the molecular mechanism is still in need of further exploration.